Sensemaking and Neuroaesthetics Neuroarts and the Spectrum of Neurodiverse Experiences - Hutson, James; Hutson, Piper; Harper-Nichols, Morgan (Springer Nature Switzerland : Imprint: Palgrave Macmillan, 2024)
XIX, 281 p. 52 illus., 49 illus. in color.